2015
DOI: 10.3151/jact.13.479
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sacrificial Point Anode for Prevention of Steel Corrosion in Cracked Concrete

Abstract: The effectiveness of a commercially available sacrificial point anode for corrosion prevention of steel in cracked concrete is presented. Reinforced concrete prisms with dimensions of 150 mm x 150 mm x 500 mm were prepared with a water to cement ratio (W/C) of 0.4 showing crack widths ranging from 0.1 to 0.4 mm obtained by pre-cracking. These specimens were exposed to three conditions: (1) laboratory air (temperature of 20±2°C and relative humidity of 60%); (2) immersed in 3% NaCl solution; and (3) dry/wet cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Even the sacrificial anodes cathodic protection is considered as the most effective and widely used in controlling chlorideinduced reinforcement corrosion [28,38,39]; however, the sacrificial anodes cathodic protection can lose its effectiveness with time due to the anode consumption during repair period [1]. The anode life is dependent on the average current output that affected by temperature, oxygen content, humidity and chloride content [40]. For the patch repaired concrete, it was reported that the sacrificial zinc anode had a profound effect on polarizing the potential of reinforcement in the substrate concrete and no significant protection in patch repair section [11].…”
Section: Introductionmentioning
confidence: 99%
“…Even the sacrificial anodes cathodic protection is considered as the most effective and widely used in controlling chlorideinduced reinforcement corrosion [28,38,39]; however, the sacrificial anodes cathodic protection can lose its effectiveness with time due to the anode consumption during repair period [1]. The anode life is dependent on the average current output that affected by temperature, oxygen content, humidity and chloride content [40]. For the patch repaired concrete, it was reported that the sacrificial zinc anode had a profound effect on polarizing the potential of reinforcement in the substrate concrete and no significant protection in patch repair section [11].…”
Section: Introductionmentioning
confidence: 99%